Epistemology of Islamic Philosophy: An Analysis and Critique of Ibn Rushd’s Epistemology - M. Chazim Munajib; Abdul Basit (International Forum of Researchers and Lecturers, 2026)
The weakness of the scientific tradition among Muslims and the complex problems of Islamic education have left Islamic education consistently lagging behind, theoretically unable to provide answers to the demands of liberalism and humanization. A reconstruction of the epistemological structure appropriate to the current context is necessary. This paper aims to analyze and critique Ibn Rushd's epistemology. The article is a study of the figure to look specifically at his epistemology with critical reasoning to produce findings on the research questions. The results of the study show that Ibn Rushd's epistemology is a critical synthesis of Greek philosophy and Islamic religion, which places reason and revelation as complementary paths to true knowledge and happiness in the afterlife. He critiques the thought that separates the two, especially by emphasizing the importance of scientific methods and rational reasoning, and highlights its critical aspects through criticism of Al-Ghazali and the development of the theory of the unity of the intellect which has had a significant impact on philosophical thought and education. Ibn Rushd's thinking sparked the Averroist movement in Europe, which later ushered in the Renaissance. His epistemology had positive implications for the development of Islamic education, encouraging the development of reason-based knowledge and scientific analysis. His concept of the unity of philosophy and religion, along with his emphasis on the scientific method, inspired scientists in the development of general knowledge in the modern era .